Hydrogel assistant synthesis of new Ti-MOF cross-linked oxidized pectin and chitosan with anti-breast cancer properties - Alkhathami, Ali G.; Khaled Younis Albahadly, Waleed; Jawad, Mohammed Abed; Ramadan, Montather F.; Alsaraf, Khulood Majid; Riyad Muedii, Zainab Al-Hawraa; Alsaikhan, Fahad; Suliman, Muath (Frontiers in Materials, 2023)
Breast cancer is one of the most common diseases of the modern age. Although many methods for its treatment have been reported so far, the report and synthesis of new compounds based on new technologies, especially nanotechnology, is important. One of the laboratory methods for evaluating the anticancer properties of compounds is the in vitro MTT method (3-(4,5-Dimethylthiazol-2-yl)-2,5-Diphenyltetrazolium Bromide). In this study, the in vitro anti-breast cancer activity of the newly synthesized (Titanium Metal-Organic Framework) Ti-MOF crosslinked oxidized pectin and chitosan hydrogel, which uses biopolymers in its synthesis and structure, was investigated. The anticancer activity results showed that the synthetic nanopolymer had cell proliferation and viability of 27% more than the control and (the half maximal inhibitory